Acceleration of energetic electrons by waves in inhomogeneous solar wind plasmas. (6th March 2017) - Krafft, C.; Volokitin, A.
Abstract : The paper studies the influence of the background plasma density fluctuations on the dynamics of the Langmuir turbulence generated by electron beams, for parameters typical for solar type III beams and plasmas near 1 AU. A self-consistent Hamiltonian model based on the Zakharov and the Newton equations is used, which presents several advantages compared to the Vlasov approach. Beams generating Langmuir turbulence can be accelerated as a result of wave transformation effects or/and decay cascade processes; in both cases, the beam-driven Langmuir waves transfer part of their energy to waves of smaller wavenumbers, which can be reabsorbed later on by beam particles of higher velocities. As a consequence, beams can conserve a large part of their initial kinetic energy while propagating and radiating wave turbulence over long distances in inhomogeneous plasmas. Beam particles can also be accelerated in quasi-homogeneous plasmas due to the second cascade of wave decay, the wave transformation processes being very weak in this case. The net gains and losses of energy of a beam and the wave turbulence it radiates are calculated as a function of the average level of plasma density fluctuations and the beam parameters. The results obtained provide relevant information on the mechanism of energy reabsorption by beams radiating Langmuir turbulence in solar wind plasmas.